USE OF A HYBRID EDUCATIONAL MODEL IN THE PROCESS OF FORMING ORAL SPEECH IN PRIMARY SCHOOL STUDENTS - Ілясов, Олександр; Гнатенко, Анастасія (SWorldJournal, 2025)
The article considers the methodological possibilities of using a hybrid educational model in the process of forming the oral speech of primary school students, in particular the use of blended learning, and analyzes the advantages of using this model, wh